2.6: Chain Rule
( \newcommand{\kernel}{\mathrm{null}\,}\)
The Chain Rule is more general than the Inverse Function Rule and deals with the case where x and y are both functions of a third variable t. Suppose x=f(t),y=G(x).
Thus x depends on t, and y depends on x. But y is also a function of t, y=g(t),where g is defined by the rule g(t)=G(f(t)).
The function g is sometimes called the composition of G and f (sometimes written g=G∘f).
The composition of G and f may be described in terms of black boxes. The function g=G∘f is a large black box operating on the input t to produce g(t)=G(f(t)). If we look inside this black box (pictured in Figure 2.6.1), we see two smaller black boxes, f and G. First f operates on the input t to produce f(t), and then G operates on f(t) to produce the final output g(t)=G(f(t)).
The Chain Rule expresses the derivative of g in terms of the derivatives of f and G. It leads to the powerful method of "change of variables" in computing derivatives
and, later on, integrals.

Let f, G be two real functions and define the new function g by the rule g(t)=G(f(t)).
At any value of t where the derivatives f′(t) and G′(f(t)) exist, g′(t) also exists and has the value g′(t)=G′(f(t))f′(t).
Proof
Let x=f(t),y=g(t),y=G(x).
Take t as the independent variable, and let Δt≠0 be infinitesimal. Form the corresponding increments Δx and Δy. By the Increment Theorem for x=f(t), Δx is infinitesimal. Using the Increment Theorem again but this time for y=G(x), we have Δy=G′(x)Δx+εΔx
for some infinitesimal ε. Dividing by Δt, ΔyΔt=G′(x)ΔxΔt+εΔxΔt.
Then taking standard parts, st(ΔyΔt)=G′(x)st(ΔxΔt)+0,g′(t)=G′(x)f′(t)=G′(f(t))f′(t).
Find the derivative of g(t)=ln(sint).
Solution
g(t) is the natural logarithm of the sine of t. It can be written in the form g(t)=G(f(t)) where f(t)=sint,G(x)=lnx.
We have f′(t)=cost,G′(s)=1x.
By the Chain Rule, g′(t)=G′(f(t))f′(t)=1sint⋅cost=costsint.
Find the derivative of g(t)=√3t+1.
Solution
g(t) has the form g(t)=G(f(t)), where f(t)=3t+1,G(x)=√x.
We have f′(t)=3,G′(x)=12x−1/2.
Then g′(t)=G′(f(t))f′(t)12(3t+1)−1/2⋅3=32√3t+1.
In practice it is more convenient to use the Chain Rule with dependent variables x and y instead of functions f and g.
Let x=f(t),y=g(t)=G(x).
Assume g′(t) and G′(x) exist. Then (i)dydt=dydxdxdt(ii)dy=dydxdt
where dx/dt, dy/dt are computed with t as the independent variable, and dy/dx is computed with x as the independent variable.
Let us work Examples 2.6.1 and 2.6.2 again with dependent variables.
Let x=sint,y=lnx.
Find dy/dt using Chain Rule (i) and dy by using Chain Rule (ii).
(i)dxdt=cost,dydx=1x,dydt=dydx⋅dxdt=1x⋅cost=costsint.(ii)dx=cost dt,dydx=1x,dy=1x dx=1xcost dt=costsint dt.
Let x=3t+1,y=√x.
(i)dxdt3,dydx=12x−1/2,dydt=dydxdxdt=32x−1/2=32(3t+1)−1/2.(ii)dx=3 dt,dydx=12x−1/2,dy=12x−1/2 dx=12(3t+1)−1/2⋅3 dt=32(3t+1)−1/2 dt.
The equation dydt=dydtdxdt
with t as the independent variable is trivial. We simply cancel the dx instances. But when dy/dx is computed with x as the independent variable while dx/dt is computed with t as the independent variable, each dx has a different meaning, and the equation is not trivial.
Similarly, the equation dy=dydxdxis trivial with x as the independent variable but not when t is the independent variable in dy and dx, while x is independent in dy/dx.
The Chain Rule shows that when we change independent variables the equations dydt=dydxdxdt,dy=dydx dxremain true.
The Inverse Function Rule can be proved from the Chain Rule as follows. Let y=f(x),x=g(y)be inverse functions whose derivatives exist. Then dydxdxdt=dydy=1,
whence dydx=1dx/dy,f′(x)=1g′(y).
Using the Chain Rule we may write the Power Rule in a general form.
Let r be a rational number, and let u depend on x. If u>0 and du/dx exists, then d(ur)dx=rur−1dudx.
This is proved by letting y=ur and computing dy/dx by the Chain Rule. dydx=dydududx=rur−1dudx.
The Chain Rule has two types of applications.
(1) Given x=f(t) and y=G(x), find dydt. Use dydt=dydxdxdt.
(2) Given x=f(t) and y=g(t), find dydx. Use dydx=dy/dtdx/dt.
Applications of type (1) often arise when a new dependent variable x is introduced to help compute dydt. Applications of type (2) arise when two variables x and y both depend on a third variable t, for example, when x and y are the coordinates of a moving particle and t is time.
We give three examples of type (1) and then three of type (2).
Suppose that by investing t dollars a company can produce x=t10−100,t≥1000,
items, and that it can sell x items for a total profit of y=5x−x2100.
Find dydt, which is the marginal profit with respect to the amount invested.
Solution
We have dxdt=110,dydx=5−x50.
By the Chain Rule, dydt=dydxdxdt=(5−x50)110=(5−t10−10050)110=0.7−t5000.
Thus after t dollars have been invested, an additional dollar will bring 0.7−t/5000 dollars of additional profit.
Find dy/dt where y=(5t2−2)1/4.
Solution
Let x=5t2−2,y=x1/4.
Then dxdt=10t,dydx=14x−3/4,dydt=dydxdxdt=(14x−3/4)(10t)=104(5t2−2)−3/4t.
Find dy/dx where y=√sin(4x+1)+cos(4x−1).
Solution
This problem requires three uses of the Chain Rule. Let u=sin(4x+1)+cos(4x−1),y=√u.
Then by the Chain Rule, dydx=dydu⋅dudx=12√u⋅dudx.
Now let v=sin(4x+1),w=cos(4x−1),u=v+w.
Then dudx=dvdx+dwdx.
We use the Chain Rule twice more to find dv/dx and dw/dx. v=sin(4x+1).dvdx=cos(4x+1)d(4x+1)dx=4cos(4x+1).w=cos(4x−1).dwdx=−sin(4x−1)d(4x−1)dx=−4sin(4x−1).
Finally, we combine everything to get dydx=12√u⋅dudx=12√u(dvdx+dwdx)=4cos(4x+1)−4sin(4x−1)2√sin(4x+1)+cos(4x−1).
If a particle is moving in the plane, its position (x,y) at time t will be given by a pair of equations x=f(t),y=g(t).
These are called parametric equations. The slope of the curve traced out by this particle can be found by the Chain Rule, dydx=dy/dtdx/dt=g′(t)f′(t),whenever the derivatives exist and f′(t)≠0. This is a Chain Rule application of type (2).
A ball thrown horizontally from a 100-foot cliff at a velocity of 50 ft/sec will follow the parametric equations x=50t,y=100−16t2,in feet.Find the slope of its path at time t (Figure 2.6.2).
Solution
dxdt=50,dydt=−32t,
so dydx=dy/dtdx/dt=−32t50.

A particle moves according to the parametric equations x=t3−t,y=t2.Find the slope of its path.
Solution
dxdt=3t2−1,dydt=2t.
Therefore, dydx=dy/dtdx/dt=2t3t2−1,t≠±√1/3.
We see from Figure 2.6.3 that the path of this particle is not the graph of a function, and in fact contains a loop and crosses the point (0,1) twice, at t=−1 and t=1. The path is vertical at the points t=±√1/3, where there is no slope. At the point (0,1), the two slopes of the path are dy/dx=−1 when t=−1, and dy/dx=1 when t=1.

A particle moving according to the parametric equations x=cost,y=sintwill move counterclockwise around the unit circle at one radian per second beginning at the point (1,0), as shown in Figure 2.6.4. Find the slope of its path at time t.

Solution
dxdt=−sint,dydt=cost.
The slope is dydx=dy/dtdx/dt=−costsint.
In terms of x and y the slope is dydx=−xy.
Problems for Section 2.6
In Problems 1-44, find dy/dx.I
1. | y=√x+2 | 2. | y=√7+4x |
3. | y=√5−x | 4. | y=√1−10x |
5. | y=1√2+3x | 6. | y=1√4−x |
7. | y=3√6x+1 | 8. | y=5√2−3x |
9. | y=√x2+1 | 10. | y=√1−x2 |
11. | y=sin(3x) | 12. | y=cos(4−2x) |
13. | y=sin(x−2) | 14. | y=cos√x |
15. | y=e4x | 16. | y=e−x2 |
17. | y=ecosx | 18. | y=ln(lnx) |
19. | y=cosu,u=ex | 20. | y=tanu,u=lnx |
21. | y=u10,1−4x | 22. | y=u−10,1−x2 |
23. | y=sinu+sinv,u=1−x2,v=2x−1 | ||
24. | y=eu+ev,1−3x,v=3−4x | ||
25. | y=eu,u=√v,v=sinx | ||
26. | y=lnu,u=tanv,v=1/x | ||
27. | y=u−1/3,u=1+√v,v=x2−1 | ||
28. | y=u−1,u=3v+4,v=1/(x+1) | ||
29. | y=u4,u=1+1/v,v=x3+1 | ||
30. | y=u2+1,u=v2+1,v=x2+1 | ||
31. | y=(√x2+1+√x2+1)1/3 | 32. | y=(x+√3−4x)−1/2 |
33. | y=3xsin(2x−1) | 34. | y=sin(2x)cos(3x) |
35. | x=cos(3t),y=sin(3t) | 36. | x=et,y=lnt |
37. | x=sint,y=sin(2t) | 38. | x=sin(et),y=cos(et) |
39. | x=ln(t+1),y=t2 | 40. | x=ecost,y=esint |
41. | x=√t2−4,y=t2 | 42. | x=1+3√t,y=2+3√t |
43. | x=3√t+1,y=3√t+2 | 44. | x=2t+1t+2,y=2t+3t+2 |
45. | A particle moves in the plane according to the parametric equations x=t2+1,y=3t3.Find the slope of its path. | ||
46. | An ant moves in the plane according to the equations x=(1−t2)−1,y=√t.Find the slope of its path. | ||
◻ 47. | Let y depend on u, u depend on v, and v depend on x. Assume the derivatives dy/du, du/dv, and dv/dx exist. Prove that dydx=dydududvdvdx. | ||
◻ 48. | Let the function f(x) be differentiable for all x, and let g(x)=f(f(x)). Show that g′(x)=f′(f(x))f′(x). |